Pharmacological Activity of Cucumis Sativus L. – A Complete Overview - Mallik, Jony; Das, Priyanka; Das, Sourav (Asian Journal of Pharmaceutical Research and Development, 2013)
Cucumber (Cucumis sativus L.) belongs to the family cucurbitaceae . There are 30 Cucumis species found in Asia and Africa. Cucumber is a native to the tropics and is one of the oldest cultivated vegetable crops. It is known in the history for over 3,000 years (Yawalkar, 1985). Cucumis sativus (CS) is growing widely throughout the Bangladesh (Forests of Gazipur, Sherpur, Chittagong, Chittagong Hill Tracts, Cox’s Bazar, Tangail and planted elsewhere), Indian subcontinent, Sri Lanka. Apparently cucumbers have originated in the foothills of the Himalayan mountains, just north of the Bay of Bengal, the area which is now primarily occupied by Bangladesh. While there does not seem to be any wild cucumbers present in the area today, scientists have identified a small bitter fruit of the squash family, which is thought to have brought forth the cucumber. Recent investigations led to the assumption that cucumbers may have started off on the African continent, however fossils, which could substantiate such claims have not yet been found. Fact is that cucumbers have already been widely cultivated in the past, which is evident from written records in many different cultures. Records show that cucumbers were already grown as far East as China as early as 2,000 years before the Christian Era. The present article attempts to provide comprehensive information on pharmacological properties of Cucumis sativus for further research. All the information were collect from the published research paper on Cucumis sativus as for the sake of future research on it.